Determination of the Optical Band gap Energy from the Extraction and Evaporation of Anthocyanin Compound Sea Lettuce (Ulva Lactuca L.) Using Tauc Plot Method - Santika, Fiar Tri; Suyanto, Hery; Trisnawati, Ni Luh Putu; Indrayana, I Putu Tedy (BULETIN FISIKA; Vol 25 No 1 (2024): BULETIN FISIKA February EditionDO - 10.24843/BF.2024.V25.i01.p02, 2024)
The optical energy gap of anthocyanin compounds from sea lettuce extract (Ulva lactuca L.) has been calculated using the Tauc plot method. Sea lettuce plants taken at Sanur Beach Bali. The sea lettuce was dried then mashed and extracted for 24 hours, the last being macerated through three cycles. The extraction results are then evaporated to obtain a thick extract solution. Extracted and evaporated-extraction samples were characterized by UV-Vis in the wavelength range of 200-800 nm. From the characterization results, it was found that the absorption of anthocyanin compounds for the extracted samples was at a wavelength of 268 and 412 nm. Meanwhile, for the extraction-evaporation sample, the absorption is at a wavelength of 286.5 and 408 nm. By using the Tauc plot method, the optical energy gap values ??for the extracted and extraction-evaporated samples were 2.69 and 2.54 eV, respectively. Therefore, anthocyanin compounds from both extracted and evaporation-extracted samples qualify as dye sensitized solar cells (DSSC) for TiO 2 semiconductors.